Thin Films: Area‐Selective Growth of HfS2 Thin Films via Atomic Layer Deposition at Low Temperature (Adv. Mater. Interfaces 23/2020). Issue 23 (3rd December 2020) - Cao, Yuanyuan; Wähler, Tobias; Park, Hyoungwon; Will, Johannes; Prihoda, Annemarie; Moses Badlyan, Narine; Fromm, Lukas; Yokosawa, Tadahiro; Wang, Bingzhe; Guldi, Dirk M.; Görling, Andreas; Maultzsch, Janina; et al.
Abstract : The 2D semiconductor hafnium sulfide, HfS2, is deposited for the first time using atomic layer deposition in mild conditions and at low temperature (100 °C). The surface reactions are specific and allow for area‐selective deposition of high‐quality thin films on self‐assembled molecular monolayers. When properly protected from air, the material is pure, stoichiometric, and ordered on a short range as deposited. More details can be found in article number 2001493 by Julien Bachmann and co‐workers.